Representative Farms Economic Outlook for the January 2019 FAPRI/AFPC Baseline - Joe L. Outlaw; George M. Knapek; J. Marc Raulston; Henry L. Bryant; Brian K. Herbst; David P. Anderson; Steven L. Klose (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2019)
The Agricultural and Food Policy Center (AFPC) at Texas A&M University develops and maintains data to simulate 94 representative crop, dairy, and livestock operations in major production areas in 30 states. The chief purpose of this analysis is to project the economic viability of those farms by region and commodity for 2019 through 2024. The data necessary to simulate the economic activity of these operations are cultivated through ongoing cooperation with panels of agricultural producers in selected states. The Food and Agricultural Policy Research Institute (FAPRI) provided projected prices, policy variables, and input inflation rates in their preliminary baseline. Under the January 2019 Baseline, 22 of the 63 crop farms are in good liquidity condition (less than a 25 percent chance of negative ending cash by 2024). Ten crop farms have between a 25 percent and a 50 percent likelihood of negative ending cash, and the remaining 31 crop farms have greater than a 50 percent chance of negative ending cash. Additionally, 41 of the 63 crop farms are in good equity position (less than a 25 percent chance of decreasing real net worth during the study period). Six crop farms have between a 25 percent and 50 percent likelihood of losing real net worth, and 16 crop farms have greater than a 50 percent probability of decreasing real net worth by 2024. The following discussion provides an overall evaluation by commodity considering both liquidity and equity measures.
Keywords: 330